Cardiopulmonary resuscitation discussions with patients admitted to acute oncology wards: A national audit of current practice. (26th March 2020) - Tol, Isabel; Cumber, Elspeth; Nakakande, Daphne; Wijaya, Silvana; Turberfield, Catherine; Badran, Abdul; Siddiqui, Safia; Srivastava, Prakhar; Chung, Bethany; Dineen, Molly; Devlin, Cariosa; Worrall, Claire; et al.
Abstract: Objectives: To map current practice regarding discussions around resuscitation across England and Scotland in patients with cancer admitted acutely to hospital and to demonstrate the value of medical students in rapidly collecting national audit data. Methods: Collaborators from the Macmillan medical student network collected data from 251 patient encounters across eight hospitals in England and Scotland. Data were collected to identify whether discussion regarding resuscitation was documented as having taken place during inpatient admission to acute oncology. As an audit standard, it was expected that all patients should be invited to discuss resuscitation within 24 hr of admission. Results: Resuscitation discussions were had in 43.1% of admissions and of these 64.0% were within 24 hr; 27.6% of all admissions. 6.5% of patients had a "do not attempt resuscitation" order prior to admission with a difference noted between patients receiving palliative and curative treatment (8.5% and 0.39%, respectively, p < .05). Discussions regarding escalation of care took place in only 29.3% of admissions. Conclusions: These data highlight deficiencies in the number of discussions regarding resuscitation that are being conducted with cancer patients that become acutely unwell. It also demonstrates the value of medical student collaboration in rapidly collecting national audit data.